Long-term Surveillance of Children with Congenital Hypothyroidism: Data from the German Registry for Congenital Hypothyroidism (AQUAPE "Hypo Dok") - Ellerbroek, V. L.; Bonfig, W.; Dörr, Helmuth-Günther; Bettendorf, M.; Hauffa, B.; Fricke-Otto, S.; Rohrer, T.; Reschke, F.; Schoenau, E.; Schwab, K. O.; Kapelari, K.; Roehl, F. -W.; et al. (Klinische Pädiatrie, 2015)
The German study group for quality assurance in pediatric endocrinology and the University of Ulm have established a software ("Hypo Dok") for the documentation of longitudinal data of patients with congenital primary hypothyroidism (CH). Aim of this study was to analyse the long-term follow-up of patients with CH and to compare treatment with current guidelines.Anonymised data of 1,080 patients from 46 centres were statistically analysed.Newborn screening result was available at a mean age of 7.3 days. Confirmation of the diagnosis was established at 8.4 days and therapy was started at 11 days. The average screening TSH was 180.0 mIU/L. During the first 3 months mean levothyroxine (LT4) dose was 10.7 µg/kg/day or 186.0 µg/m²/day. Weight-, BMI- and height-SDS did not differ significantly from the normal population. Only 25% of the patients (n=262) underwent formal EQ/IQ-testing. Their average IQ was 98.8 ± 13.2 points.In Germany screening, confirmation and start of treatment of CH are within the recommended time frame of 14 days. Initial LT4-doses are adequate. The auxological longterm outcome of young CH patients is normal. The implementation of standardized IQ testing has to be improved in routine patient care.Longitudinal data of patients with CH was analysed and compared to current guidelines. Confirmation and start of treatment are according to the recommendations. However standardised IQ testing requires improvement.
EVALuna2:18917